Assessment of atherosclerosis and endothelial dysfunction risk factors in patients with primary glomerulonephritis - Hagemann, Rodrigo [UNESP]; Watanabe, MarcelaTatiana [UNESP]; Hueb, João Carlos [UNESP]; Martín, Luis Cuadrado [UNESP]; Silva, Vanessa dos Santos [UNESP]; Teixeira Caramori, Jacqueline do Socorro Costa [UNESP] (FapUNIFESP (SciELO), 2024)
Introduction: Glomerulonephritis are the third cause of chronic kidney disease (CKD) requiring dialysis in Brazil. Mineral and bone disorder (MBD) is one of the complications of CKD and is already present in the early stages. Assessment of carotid intima-media thickness (CIMT) and flow-mediated vasodilatation (FMV) are non-invasive ways of assessing cardiovascular risk. Hypothesis: Patients with primary glomerulonephritis (PG) have high prevalence of atherosclerosis and endothelial dysfunction, not fully explained by traditional risk factors, but probably influenced by the early onset of MBD. Objective: To evaluate the main markers of atherosclerosis in patients with PG. Method: Clinical, observational, cross-sectional and controlled study. Patients with PG were included and those under 18 years of age, pregnants, those with less than three months of follow-up and those with secondary glomerulonephritis were excluded. Those who, at the time of exams collection, had proteinuria higher than 6 grams/24 hours and using prednisone at doses higher than 0.2 mg/kg/day were also excluded. Results: 95 patients were included, 88 collected the exams, 1 was excluded and 23 did not undergo the ultrasound scan. Patients with PG had a higher mean CIMT compared to controls (0.66 versus 0.60), p = 0.003. After multivariate analysis, age and values for systolic blood pressure (SBP), FMV and GFR (p = 0.02); and FMV and serum uric acid (p = 0.048) remained statistically relevant. Discussion and conclusion: The higher cardiovascular risk in patients with PG was not explained by early MBD. Randomized and multicentric clinical studies are necessary to better assess this hypothesis.
Avaliação dos fatores de risco de aterosclerose e disfunção endotelial em pacientes com glomerulopatias primárias
Keywords: Bone Disorder; Cardiovascular diseases; Chronic; Chronic Kidney Disease-Mineral; Glomerulonephritis; Renal Insufficiency